PENGARUH RELATED PARTY TRANSACTION, KEPEMILIKAN MANAJERIAL, DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE - Nadya Aribah, (2023)
This study was conducted to analyze the effect of related party transactions, managerial ownership, and fiscal loss compensation on tax avoidance in manufacturing companies in Indonesia. The technique used was purposive sampling and a total of 355 samples were obtained. This type of research is quantitative using secondary data sourced from annual reports and company financial statements. The data analysis technique used is multiple linear regression analysis using Stata Version 16 software. The results of this study indicate that related party transactions, fiscal loss compensation do not have a significant effect on tax avoidance. The next result, managerial ownership has a significant negative effect on tax avoidance which shows that the higher the proportion of share ownership by management is able to minimize the occurrence of tax avoidance activities.